Analisis Tingkat Kerusakan Tanaman Jati (Tectona grandis L.f) Akibat Serangan Hama di Kelurahan Klamalu Distrik Mariat Kabupaten Sorong: Analysis of Damage Levels of Teak Plants (Tectonagrandis L.f) Due to Pest Attack in Klamalu Village, Mariat District, Sorong Regency - Pattiwael, Maya (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Teak (Tectona grandis L.f) is one of the tropical plants that have high economic value. Teak plants are also often attacked by various types of pests, which results in a decrease in the quality and quantity of growth and yield. This research was conducted aimed at identifying the types of pests that damage the leaves of teak plants and determine the intensity of damage and frequency of pest attacks on teak plants located in Klamalu Village, Mariat District, Sorong Regency. Data retrieval is done by dividing five simple random lines, five plots taken as samples. The results showed several types of pests that attacked teak plants namely grasshoppers, aphids, teak leaf caterpillars, and white mites, with an average damage intensity due to the attack of locust pests 28.93% classified as moderate damage, caterpillar pest attack 22.53 % was classified as a criterion of mild impairment, 6.8% white flea pest attacks classified as criteria for minor damage and infestation attacks 5.7% were classified as criteria for minor damage. The frequency of attacks for each type of pest is Grasshopper Pests 35.2%, Teak Leaf Caterpillar Pests 30.4%, White Louse Pests 8.8% and Leaf Louse Pests by 4%